Durability of epoxy concrete under Malaysian atmosphere - Teh, T.K (Universiti Malaysia Sarawak, UNIMAS, 2009)
Strength in concrete is the main concern in concrete technology and its advancement. In the recent decades, durability had become a crucial aspect in concrete especially it was exposed to Malaysian Atmosphere. Many development and techniques were improvised to enhance concrete strength and durability. One of the methods to gain both traits in concrete is by adding epoxy in the concrete mixture. In Malaysia, epoxy concrete is relatively new, and thus experimental investigations need to be conducted to understand in depth how its responses under Malaysian conditions. A study was conducted to investigate the durability and development of strength of epoxy concrete under Malaysian Atmosphere. 6 series of samples were prepared with various contents of epoxy concretes, 100×100×100 mm and 150×150×150 mm were casted by using Sikadur-52 as the epoxy. Pure mortar acts as control sample. The concretes were compared and tested with compressive strength test, weather effect tests, acid attack test and permeability test to see development of strength of epoxy concrete. It was found that the epoxy was effective in binding the aggregates and cement where the development of strength was increased. The epoxy was able to increase the strength of the concrete where the higher content of epoxy will return the strength much higher if compared with lower content of epoxy and pure mortar. Also it was found out that epoxy will give a lower permeability compared with the pure mortar. Changes in dimensions and density were also affected in the acid resistance test. It can be concluded that the effects on the epoxy concrete is influenced by the content of epoxy.